Analisis Manajemen Kejadian Stunting pada Balita di Desa Waesamu Tahun 2023 - Zulfikar Lating; Mariene Wiwin Dolang; Epi Dusra; Hamka Hamka; Wa Ode Satriawati Saendrayani (Jurnal Medika Husada, 2023)
Stunting is a condition that describes chronic malnutrition during the growth and development of children. Globally, around 149,2 million children under five suffer from stunting. Indonesia has the highest prevalence of stunting among children with middle and lower economies. The aim of this research is to analyze the management of stunting events in toddlers in Waesamu village, West Kairatu sub-district, West Seram Regency in 2023. The type of research used is a qualitative research method which is a research procedure that produces descriptive data. The informants in this study used key informants, namely the holders of the West Kairatu Health Center nutrition program and mothers of stunted toddlers who were in the village of Waesamu while the supporting informants were the head of the village of Waesamu. Data collection procedures carried out through interviews (interviews). The implementation of stunting programs in Waesamu village has been carried out well. The evaluation results showed that the number of stunted children under five in Waesamu village was 11 people and there were further assistance and intervention steps for stunting cases with the hope that it would reduce the stunting rate in Waesamu village. The obstacle in the management of stunting in Waesamu village is the lack of participation from pregnant women and toddlers who rarely visit the Posyandu. It is better if stunting is not only paid attention to by health workers but all stakeholders in the village, especially the community, who must pay attention to the surrounding environment so that they can support the village government and health workers to reduce the stunting rate in Waesamu village.